Intracranial lipoma manifesting with change in preexisting headache characteristics - Santos, Patrick Emanuell Mesquita Sousa; Silva, Ivan Rodrigues; Peres, Mário Fernando Prieto; Silva-Néto, Raimundo Pereira (Headache Medicine, 2019)
Intracranial lipomas represent 0.1% to 0.5% of all intracranial tumors. Approximately half of the patients are asymptomatic. In symptomatic patients, headache is the most common symptom. We describe the case of a 71-year-old woman with history of generalized seizures and episodic migraine for about 30 years. In recent months, there has been a change in the characteristics of headache. She was admitted to the emergency room with muscle weakness in left hemibody and intense headache onset approximately four hours ago. Neuroimaging exams revealed a median frontal expansive lesion suggestive of intracranial lipoma.